2020
DOI: 10.5267/j.msl.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of empowerment in improving internal process, customer satisfaction, learning and growth

Abstract: The objective of this research was to identify the role of empowerment in enhancing Safeway Company's performance in Jordan using structural equation model (SEM). The authors used a predictive-descriptive strategy to determine Safeway Company's levels of empowerment. To evaluate the role of empowerment and performance, a questionnaire was designed and circulated. The data were examined using means, standard deviations, and multiple linear regression analyses. Empowerment and its dimensions from the Safeway com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…These authors argued that the BSC has to be correctly parameterized to identify who is responsible to implement tasks within the organization. Other authors suggested that the BSC sheds light on the identification of inappropriate strategic decisions and can enhance the feedback from managers (Al-Omari et al, 2020). The managers may rely on the key performance indicators, "as the BSC's dashboards become like a laboratory to truly optimize size and complexity" (Cokins, 2013, p.72).…”
Section: Balanced Scorecard -Aligning the Stakeholders' Objectivesmentioning
confidence: 99%
“…These authors argued that the BSC has to be correctly parameterized to identify who is responsible to implement tasks within the organization. Other authors suggested that the BSC sheds light on the identification of inappropriate strategic decisions and can enhance the feedback from managers (Al-Omari et al, 2020). The managers may rely on the key performance indicators, "as the BSC's dashboards become like a laboratory to truly optimize size and complexity" (Cokins, 2013, p.72).…”
Section: Balanced Scorecard -Aligning the Stakeholders' Objectivesmentioning
confidence: 99%
“…Keeping up a serious edge in a worldwide, inventive and powerfully developing condition produces strain to rethink how business is led (Ulijn et al, 2000). Over various years, ranking directors have gotten progressively worried about the changing idea of their authoritative surroundings and how they can recognize and follow up on such changes in the earth (Davis, 2002;Malkawi, et al 2017;Al-Omari, et al, 2020). In any case, right now, results of progress are not constantly unsurprising and the earth is dynamic, making the identification of progress considerably more troublesome (Grewal and Tansuhaj, 2001).…”
Section: Literature Review Strategic Thinkingmentioning
confidence: 99%
“…Responsibility is perceived as an ethical behavior that is linked to the environmental pollution issues, unemployment, inflation, and increasing poverty among some social minorities, and established of social responsibility in this aspect of the failure of the business organizations to implement its duties towards society the Arab Society of Certified Public Accountants (Fassin et al, 2011). Al-Omari, et al (2020) defines social responsibility as a set of decisions and actions taken by the organization to achieve the desired goals and values of the community, which are part of the direct economic organization management benefits that are part of its strategy. According to Friedman, M. (2007), there is an overlapping relationship between social responsibility and business ethics, which appeared in late seventies of the last century, when the focus on the ethics management as well as social responsibility and efficiency began.…”
Section: Theoretical Frameworkmentioning
confidence: 99%